2020
DOI: 10.17826/cumj.702020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training on stress and coping with stress in patients receiving infertility treatment

Abstract: ÖzPurpose: This study was planned and applied semiexperimentally to examine the effect of education given to patients receiving infertility treatment on stress and coping with stress. Materials and Methods:The study is semi-experimental. It was held between May 2017 and January 2018 with individuals who applied to a foundation hospital in Istanbul province for IVF treatment. The sample was made up of 40 infertile individuals. The data were collected by the researcher through face-to-face interview method. Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Eroğlu and Temiz (2020) found that stress increases as the use of active-avoidance, active confronting and passiveavoidance coping methods, which are dimensions of the scale, increases in infertile women. The finding of this study was compatible with that reported by Eroğlu and Temiz [34]. Knowing the coping methods used by infertile couples is important in terms of supporting effective coping methods and planning interventions to abandon ineffective coping methods.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Eroğlu and Temiz (2020) found that stress increases as the use of active-avoidance, active confronting and passiveavoidance coping methods, which are dimensions of the scale, increases in infertile women. The finding of this study was compatible with that reported by Eroğlu and Temiz [34]. Knowing the coping methods used by infertile couples is important in terms of supporting effective coping methods and planning interventions to abandon ineffective coping methods.…”
Section: Discussionmentioning
confidence: 96%
“…Peterson, et al (2006) stated that, while the typical coping mechanism of men is distancing and self-control, women prefer professional support, social support and taking responsibility. It was shown that active avoidance among coping behaviors may be a predictor of high stress caused by fertility problems [34]. It has been reported that women with low education levels used passive coping methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation